Governance and Culture – A New Approach to Understanding Structures of Collaboration - Söpper, Katharina (European Spatial Research and Policy, 2014)
The paper aims to contribute to a better understanding of structures of collaboration and their underlying logic by combining theories on Governance and (Planning) Culture. By the introduction of an integrative approach, called the ‘The Culture-Based Governance Analysis’, aspects of both discourses are combined. Factors from the Governance discourse, providing analysis on the frameworks of collaboration, were integrated with factors from the Culture discourse, providing analysis of the underlying reasons for people collaborating or not. This novel approach provides a way to analyze and understand how existing collaborations have developed and the basis on which they operate. As a further step, it enables planners to use this knowledge for the establishment of future collaborations between already active as well as not yet involved actors, for example, in urban redevelopment processes.